2017
DOI: 10.1080/07347332.2017.1340389
|View full text |Cite
|
Sign up to set email alerts
|

Experience of grief by patients with cancer in relation to perceptions of illness: The mediating roles of identity centrality, stigma-induced discrimination, and hopefulness

Abstract: Diagnosis of cancer leads to multiple losses, all with the potential to initiate grief reactions in patients. The present study aims to contribute to the understanding of the experience of grief by patients with cancer in relation to perceptions of illness, with a focus on the mediating roles of identity centrality, stigma-induced discrimination, and hopefulness. The analyses indicated that these factors functioned as significant partial mediators. The results have implications in terms of supporting patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 100 publications
0
19
0
Order By: Relevance
“…The women in this study experienced loss physically or psychologically in varied degrees, and hence they were likely to demonstrate some features of coping with grief when adjusting with their breast cancer diagnosis. While grief reaction to a cancer diagnosis is well documented (Glaser et al, 2019; Gökler-Danışman et al, 2017; Vergo et al, 2017), it has not been identified as a part of PTG.…”
Section: Discussionmentioning
confidence: 99%
“…The women in this study experienced loss physically or psychologically in varied degrees, and hence they were likely to demonstrate some features of coping with grief when adjusting with their breast cancer diagnosis. While grief reaction to a cancer diagnosis is well documented (Glaser et al, 2019; Gökler-Danışman et al, 2017; Vergo et al, 2017), it has not been identified as a part of PTG.…”
Section: Discussionmentioning
confidence: 99%
“…The previously validated six‐item State Hope Scale is a dispositional measure of hope. This scale has previously been used in a general oncology setting . Although conceptually similar to optimism and resilience, prior research has demonstrated that hope, optimism, and resilience are related but all uniquely contribute to positive outcomes, suggesting that they are not identical constructs .…”
Section: Methodsmentioning
confidence: 99%
“…The main factors that seem to affect specificity are emotional distress such as depression and impaired cognitive functioning (Williams et al, 2007). Thus, the higher levels of depressive symptomatology and reduced executive functioning associated with and predicting specificity in the sample of cancer patients coincide, on one hand, with the findings of studies that report the disease induces drastic changes, interferences in life purposes (Abrams, Hazen & Penson, 2007) and multiple losses underlying depression or grief reaction (Gökler-Danışman, Yalçınay & Yiğit, 2017).…”
Section: Discussionmentioning
confidence: 62%
“…Cancer also generates major psychosocial challenges that impact the economic, physical, psychological and social well-being of patients (Jacobsen & Andrykowski, 2015). In most cases, the disease involves the patient having to take on a new personal role with implications for their psychological adjustment, especially when the cancer experience becomes central to their identity (Gökler-Danışman, Yalçınay & Yiğit, 2017; Park, Bharadwaj & Blank, 2011). When people recall their past in association with life-threatening concerns or conflicts such as a disease process, their self-defining memories (SDMs), which are memories that help oneself and significant others to understand who one is as a person (Singer & Moffitt, 1992), tend to be representative of these events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation